Carbon nanodots functional MOFs composites by a stepwise synthetic approach: enhanced H2 storage and fluorescent sensing. Issue 5 (15th December 2014) - Li, Ji-Sen; Tang, Yu-Jia; Li, Shun-Li; Zhang, Shu-Ran; Dai, Zhi-Hui; Si, Ling; Lan, Ya-Qian
Abstract : The carbon nanodots functional UMCM-1 composites (Cdots@UMCM-1a) were first synthesized by a stepwise synthetic approach, which enhanced H2 storage capacity and exhibited highly fluorescent sensing for nitroaromatic explosives. Abstract : Metal–organic frameworks (MOFs) hybrid composites, combining the advantages of both MOFs and nanoparticles, may exhibit unprecedented properties. Herein, carbon nanodots (Cdots) functional UMCM-1 composites (Cdots@UMCM-1a) were successfully synthesized by a stepwise synthetic approach for the first time. The hybrids retain the intact structure of MOFs with high luminescence and longer stability. Due to the interactions between polar functional groups at the surface of the Cdots and H2 molecules, Cdots@UMCM-1a efficiently enhanced H2 storage capacity. Most importantly, Cdots@UMCM-1a exhibited highly fluorescent sensing for nitroaromatic explosives owing to the double effect of porous MOFs and fluorescent Cdots. This work will pave new avenues for the fabrication of novel and multifunctional MOFs composites.